Busca de substâncias inseticidas e fungicidas para controle de formigas-cortadeiras através do estudo fitoquímico biomonitorado de espécies de Picramnia e avaliação da atividade bacteriostático em Xanthomonas citri subsp citri - Cruz, Artur da Silva (Universidade Federal de São Carlos, 2019)
The search for insecticide and fungicide substances to control leaf-cutting ants through biomonitored phytochemical study of Picramnia species and evaluation of bacteriostatic activity in Xanthomonas citri. Subsp citri. The search for substances with potential activity is the target of numerous studies within the chemistry of natural products, ranging from structural elucidation to the mechanism of action. Some Picramnia species have a variety of class of secondary compounds, generating interest in their application, justifying the study of this family. The species Picramnia riedelle has little study regarding its chemical composition and biological activity of its constituents. In this context, this work was developed in order to perform biomonitored study of Pricamnia riedelle extracts, seeking isolated active principles and characterizing them. Thus, the activity of methanolic extracts of leaves and branches, fractions and some isolated substances was evaluated, performing fungicide, insecticide and bacterial assays. We identified in this work 4 long chain acids, 4 long chain esters and 5 anthraquinones, together with the synthesis of a new metal complex with an anthraquinone as the ligand, the first time the report of such a molecule formed. Together with the aid of the centrifugal partition chromatography technique used for the fractionation of methanolic leaf extract.
Search for insecticidal and fungicidal substances to control leaf-cutting ants through the biomonitored phytochemical study of Picramnia species and evaluation of bacteriostatic activity in Xanthomonas citri subsp citri
Keywords: Fitoquímica; Antraquinonas; Inseticidas naturais; Fungicida; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::QUIMICA DOS PRODUTOS NATURAIS